Analisis Pengembangan Karier yang Dipengaruhi oleh Kepemimpinan, Budaya Organisasi, dan Prestasi Kerja - Boge Triatmanto (University of Merdeka Malang, 2017)
This research is an explanatory of causality in the public organization, aims to analyze the influence of leadership, organizational culture and employess performance to career development and to analyze the dominant influence among leadership, organizational culture and employess performance to career development. The population in this study are employees of government organizations. The sampling technique is a census where all the populations (62 employees) become sample. The results of this study shows that leadership, organizational culture, and employess performance significantly influence career development. Employess performance is the dominant variable affecting the career development of employees. The key of career development is the employess performance, therefore the organization should always improve the skills and knowledge of their employess through education and training, so that employees can improve their performance from time to time. It will determine the development of their career. https://doi.org/10.26905/jmdk.v5i2.1874